Peranan Sistem Informasi dengan Online Trading terhadap Pertumbuhan Pasar Modal di Indonesia - Tarigan, Riswan Efendi (Bina Nusantara University, 2013)
Capital Markets is part of the financial market, which is related to the supply and demand of the need for long-term funding. Capital Markets was formed and developed with aims to support the implementation of national development in order to improve the distribution, growth, and stability of the national economy towards the improvement of society welfare. However, so far the capital market in Indonesia is still around 0.5% of the total population which is too small compared to capital markets in other advanced countries. One solution for increasing community involvement in the capital market, despite educating in smart and sustainable way, is developing and implementing efficient information systems, so that made it easier for market participants to undertake investment activities. This paper examines how and to what extent the role of information system enhances the capital market in Indonesia, which aims to plan the subsequent strategic step so that the development of Indonesia?s capital market is able to compete in globalmarket.